Geosynthetic-reinforced soil check dam: Case study and numerical analyses - Hsin-Ming Wu; Kuo-Hsin Yang; Chen-Cheng Kao; Chaicharn Thongthanawat; Suched Likitlersuang; Jyun-Yen Wang; Feng-Chi Huang; Wei-Lung Huang; Ching-Shui Kuo (Geotextiles and Geomembranes, 2026)

Probabilistic seismic hazard assessment for Taiwan: Updates and improvements in TEM PSHA2025 - Jia-Cian Gao; Jo-Chen Kao; Chung-Han Chan; Ray Y. Chuang; Cheng-Hung Chen; J. Bruce H. Shyu; Kuo-En Ching; Yu Wang; Kuo-Fong Ma (Engineering Geology, 2026)

Correction: Volatile Compounds from Endophytic PGPM Improve Copper Tolerance by Regulating Redox Balance in Cauliflower - Jing-Yu Chen; Tri-Phuong Nguyen; Chih-Cheng Lin; Ching-Han Chang; Hieng-Ming Ting; Ping-Fu Hou; Hao-Jen Huang (Journal of Plant Growth Regulation, 2026)

Chlorpyrifos exposure induced cytotoxic death in pancreatic islet β-cells via the functional co-activation of JNK and AMPKα signaling downstream-mediated mitochondria-dependent apoptosis pathway - Ching-Yao Yang; Kuan-I Lee; Ya-Wen Chen; Shing-Hwa Liu; Kai-Min Fang; Chun-Ying Kuo; Wei-Cheng Lia; Kai-Chih Chang; Jun-An Ke; Cheng-Tien Wu; Chun-Fa Huang; Chin-Chuan Su (Food and Chemical Toxicology, 2026)

Volatile Compounds from Endophytic PGPM Improve Copper Tolerance by Regulating Redox Balance in Cauliflower - Jing-Yu Chen; Tri-Phuong Nguyen; Chih-Cheng Lin; Ching-Han Chang; Hieng-Ming Ting; Ping-Fu Hou; Hao-Jen Huang (Journal of Plant Growth Regulation, 2026)

Coupled oxygen and nitrogen defect sites in Co-N4-coordinated frameworks facilitate stepwise CO2 methanation - Pin-Yu Liu; Sheng-Xiang Chou; Wei-Tse Sun; Hsin-Han Chen; Cheng-Hung Tsai; Yen-Lin Lai; Yu-Cheng Shao; Chi-Liang Chen; Yu-Ching Huang; Yun-Wei Chiang; Bo-Hong Liu; Chia-Hsin Wang; et al. (Chemical Engineering Journal, 2026)

Atomic-scale CuOx–Fe3O4₋x/TiO2 heterostructures with defect synergy for highly selective and efficient reverse water–gas shift reaction - Po-Wen Cheng; Fa-Chih Pai; Chien-Yi Liu; Chih-Wei Hu; Ching-Yi Chou; Guo-Wei Lee; Chia-Shing Wu; Chun-Hong Kuo; Kuang-Kuo Wang; Po-Chun Chen; Tsan-Yao Chen (Chemical Engineering Journal, 2026)

STAT3 Signaling Mediates Agomelatine Restoration of Prefrontal Cortex Synaptic Plasticity in Chronic Social Defeat Stress Mice - Chi-Wei Lee; Han-Fang Wu; Hsin-Ju Yen; Lun-De Liao; Wei-Chang Mao; Hsun-Shuo Chang; Yih-Fung Chen; Chia-Hsien Lin; Cheng-Ta Li; Hui-Ching Lin (Molecular Neurobiology, 2026)
Major depressive disorder (MDD) is a major public health issue worldwide. It not only causes an increased socio-economic burden, but also negatively affects personal lives. It has been shown that depression leads to impairments in synaptic plasticity, such as impaired long-term potentiation (LTP) in the prefrontal cortex (PFC). A recent study reported that administration of agomelatine, a melatonin receptor agonist and 5-hydroxytryptamine (5-HT) 2C antagonist, which may be involved in synaptic functions, for 1 week has a rapid antidepressive effect. Moreover, the mechanism of Glycogen synthase kinase 3β (GSK3β), regulated by signal transducer and activator of transcription 3 (STAT3), may play an important role in the synapse-related pathological mechanisms of depression. Hence, we used chronic social defeat stress (CSDS) as an animal model of depression, to investigate whether synaptic plasticity impairment in depression, improved by agomelatine, is mediated through the STAT3 mechanism. The results showed that depressive-like behaviors were reversed after 1 week of agomelatine treatment. Moreover, the impairment of LTP and alteration of spine density were reversed by agomelatine in the PFC. We further applied AG490, an inhibitor of STAT3, to demonstrate that the therapeutic mechanism of agomelatine improves synaptic plasticity through STAT3-regulated phosphorylation of GSK3β. Taken together, these results demonstrated that STAT3-regulated downstream molecules are potential therapeutic targets for the rapid action of antidepressants.

WSSV regulates malate-aspartate shuttle during infection - Yen Siong Ng; Fang-Jyun Guo; Kuan-Lun Huang; Cong-Yan Chen; Shu-Wen Cheng; Han-Ching Wang (Fish & Shellfish Immunology, 2025)

Alkylammonium ligands-driven perovskite lattice engineering for white perovskite nanocrystals single emitters - Jean-Sébastien Bénas; Zhen-Li Yan; Wei-Cheng Chen; Chu-Chen Chueh; Jing-Yan Wu; Wei-Wen Chen; Fang-Cheng Liang; Erdi Akman; Yu-Jung Lu; Yen-Yu Wang; Ja-Hon Lin; Ye Zhou; et al. (Chemical Engineering Journal, 2025)

Empagliflozin attenuates sorafenib-promoted renal ferroptosis and inflammation by targeting cyclooxygenase-2/prostaglandin E2 axis - Ming-Kai Tsai; Wen-Chin Lee; Shih-Chung Huang; Chao-Cheng Huang; Yi-Chen Wang; Chien-Han Yuan; Chih-Chiang Wang; Ching-Han Liu; Nan-Chieh Huang; Yi-Chen Chang; Cheng-Chieh Fang; Bi-Wen Yeh; et al. (Toxicology and Applied Pharmacology, 2025)

Gastrointestinal stability and DPP-IV inhibitory activity of tilapia (Oreochromis niloticus) viscera hydrolysate-derived novel peptides LPCL and TPFLPDE, with LPCL-modulated GLP-1 and PepT1 expression in STC-1 cells - Rhessa Grace Guanga Ortizo; Ching-Shu Lai; Choirul Anwar; Vishal Sharma; Pei-Pei Sun; Chiu-Wen Chen; Cheng-Di Dong; Mei-Ling Tsai (Food Research International, 2025)

Epigenetic transgenerational effects of prenatal exposure to 2,2′,4,4′-tetrabromodiphenyl ether on sperm function and DNA methylation in rat offspring - Ching-Shu Lai; Wei-Cheng Hsu; Jenq-Renn Chen; Bing-Mu Hsu; Kuo-Hsin Lee; Ping-Hsun Wu; Ping-Chi Hsu (Food and Chemical Toxicology, 2025)

Sol-gel assisted synthesis of rare earth (4f)‐transition metal (3d) binary metal oxide: Application to electrocatalytic oxidation of carbamate insecticide - Yamunadevi Kandeepan; Tse-Wei Chen; Sivaprakash Sengodan; Shen-Ming Chen; Wei-Ching Cheng (Process Safety and Environmental Protection, 2025)

Hyperbaric oxygen therapy attenuates carbon monoxide-induced lung injury by restoring mitochondrial dynamics and suppressing Pink1/Parkin-mediated mitophagy - Tzu-Hao Chen; Chien-Chin Hsu; Ching-Ping Chang; Chien-Cheng Huang; Ying-Jan Wang (Environmental Pollution, 2025)

Enhanced Hair Growth Through Transdermal Delivery of Bacopa Monnieri Extract Using a Needle-Free Supersonic Atomizer - Yu-Chiuan Wu; Yi-Ping Lin; Ching-Yi Chang; Hsia-Ying Cheng; Tien-Huei Chu; Chien-Chih Chen; Shyh-Ming Kuo (Journal of Medical and Biological Engineering, 2025)

Polycyclic aromatic hydrocarbon-aryl hydrocarbon receptor signaling regulates chronic inflammation in lung-gut axis - Tzu-Yu Cheng; Ching-Shan Luo; Po-Hao Feng; Kuan-Yuan Chen; Chih-Cheng Chang; Nguyen Van Hiep; Yueh-His Chen; Yun-Kai Yeh; Sheng-Ming Wu (Toxicology and Applied Pharmacology, 2025)

Microplastic-induced hypertension in rats: A two-hit model exploring oxidative stress and gut microbiota - Yu-Chun Cheng; Wei-Ling Chen; Hong-Ren Yu; Ching-Yi Tsai; Jiunn-Ming Sheen; Mao-Meng Tiao; Chien-Ning Hsu; You-Lin Tain (NanoImpact, 2025)

Effects of pterostilbene on inducing apoptosis in normal bladder and bladder cancer cells - Chen-Hsun Ho; Chia-Kwung Fan; Yi-Chen Chu; Shih-Ping Liu; Po-Ching Cheng (Tissue and Cell, 2025)

A potential closed-loop reutilization of iron sludge for wastewater treatment through the solid state reaction with spent coffee grounds - Kun Qin; TsingHai Wang; Wei-Tong Li; Zi-Ying Lu; Cheng-Yu Li; Wei-Fan Kuan; Jenn-Fang Su; Ching-Lung Chen (Process Safety and Environmental Protection, 2025)

Fabrication of sesamin-loaded sodium caseinate nanoparticles: Insight to characterization, in vitro digestion, and molecular docking analysis - Wan-Yi Liu; Tzu-Yu Chen; Yun-Shan Hsieh; Yung-Yi Cheng; Shiou-Ling Li; Li-Ching Chang; Yu-Tse Wu (Food Bioscience, 2025)

Pixel array-based urine biosensor for detection of trimethylamine N-oxide and glucose for early detection of diabetic kidney disease - Mei-Ching Yu; Chi-Jen Lo; Wei-Cheng Lin; Wei-Lun Yen; Yun-Yu Hsieh; Bing-Hong Chen; Fu-Sung Lo (Analytica Chimica Acta, 2025)

3D Bismuth oxyhalide flowers intertwined 1D graphitic carbon fibers catalyst: A disposable electrochemical sensor for the detection of carcinogenic 3,3′,5,5′-Tetrabromobisphenol A in water samples - Thangavelu Sakthi Priya; Tse-Wei Chen; Shen-Ming Chen; Wei-Ching Cheng (Process Safety and Environmental Protection, 2025)

BTEX exposure and metabolite levels in Taiwan schoolchildren near petrochemical areas - Wei-shan Chin; Ching-chun Huang; Yu-cheng Chen; Jing-fang Hsu; Chih-Da Wu; Pinpin Lin; Pau-chung Chen; Yue Leon Guo (International Journal of Hygiene and Environmental Health, 2025)

ONC201 exerts oncogenic effects beyond its mitochondria-disturbing role in neuroblastoma subsets - Jyun-Hong Jiang; Yu-Han Lin; Pei-Lin Liao; Ting-Ya Chen; Hui-Ching Chuang; Chao-Cheng Huang; Wen-Ming Hsu; Jiin-Haur Chuang; Wei-Shiung Lian (Journal of Molecular Medicine, 2025)
Neuroblastoma (NB) is a formidable challenge in pediatric oncology due to its intricate molecular landscape, necessitating multifaceted therapeutic approaches. ONC201 is an imipridone antibiotic compound with a promising drug candidate leveraging its potent anticancer properties against the mitochondrial proteases ClpP and ClpX. Despite demonstrating early clinical promise, particularly in MYCN -amplified NB, its efficacy in non- MYCN -amplified NB remains a subject worthy of investigation. In this study, we extended the coverage of ONC201 to treat non- MYCN -amplified NB, and our data implicated ONC201’s inability to reduce tumor growth in animal models harboring SK-N-AS or SK-N-FI cell lines. Interestingly, ONC201 induced the expression of oncogenic markers c-Myc and LGR5 while downregulating the tumor suppressor ATRX. While it fails to attenuate tumor neovascularization in non- MYCN -amplified NB xenografts, its effectiveness differs from that of its MYCN-amplified counterpart. Rho zero (ρ0)-SK-N-AS cells treated with ONC201 showed comparable observed trends in parental SK-N-AS cells, including LGR5 upregulation and ATRX downregulation, suggesting that ONC201’s multifaceted actions extend beyond mitochondrial targets. Our elucidation highlights the need to discern molecular signatures when deploying ONC201 monotherapy against NB, which lacks MYCN- amplification.

4-Anilinoquinolinylchalcone derivatives mediate antifibrotic effects through ERK/MRTF—a signaling pathway crosstalk - Padhmavathi Selvam; Chih Hua Tseng; Ching Tung Wang; Yu-Yo Sun; Yeh-Long Chen; Yu-Tse Kao; Hans-Uwe Dahms; Chih Mei Cheng (Environmental Science and Pollution Research, 2025)

The herbicide 2,4-dichlorophenoxyacetic acid induces pancreatic β-cell death via oxidative stress-activated AMPKα signal downstream-regulated apoptotic pathway - Ken-An Lin; Chin-Chuan Su; Kuan-I Lee; Shing-Hwa Liu; Kai-Min Fang; Chih-Hsin Tang; Wei-Cheng Lia; Chun-Ying Kuo; Kai-Chih Chang; Chun-Fa Huang; Ya-Wen Chen; Ching-Yao Yang (Toxicology Letters, 2025)

Proximity to petrochemical industry and risk of childhood asthma occurrence - Shih-Chun Pan; Wei-Shan Chin; Ching-Chun Huang; Yu-Cheng Chen; Chih-Da Wu; Chin-Yu Hsu; Pinpin Lin; Pau-Chung Chen; Yue Leon Guo (International Journal of Hygiene and Environmental Health, 2025)

Safety evaluation of Limosilactobacillus fermentum PS150 for use as a commercial psychobiotic - Li-Hao Cheng; Chien-Chen Wu; Chin-Lin Huang; Yu-Hsuan Wei; Pei-Jun Wen; Shih-Hau Chiu; Chien-Chi Chen; Ching-Ting Lin; Po-Lin Liao (Food and Chemical Toxicology, 2025)

Fire dynamics, fire generated pollutants, and acute health implications: A scaling law analysis of heavy-fuel-oil pool fires - Kuang-Chung Tsai; Li-Hsin Cheng; Chi-Fu Yeh; Tzu-Yan Tseng; Tzu-Ping Tseng; Li-Jen Huang; Shu-Hsing Yeh; Hui-Tsung Hsu; Ching-Ho Lin; Chin-Hsing Lai; Peter Brimblecombe; Ming-Jen Chen (Fuel, 2025)

Ambient stable ZnBr2-assisted lead-free perovskite for enhanced piezoelectricity of polyvinylidene fluoride in versatile piezo-phototronic applications - Manikandan Venkatesan; Wei-Chun Lin; Wei-Cheng Chen; Jayashree Chandrasekar; Yu-Hang Huang; Kai-Wei Lin; Zih-Syuan Syu; Ja-Hon Lin; Wei-Hung Chiang; Wei-Ren Liu; Ye Zhou; Chi-Ching Kuo (Chemical Engineering Journal, 2025)

Highly active Cu-embedded in magnetic carbon nanofibers for the reduction of 4-nitrophenol - Ching-Shiun Chen; Tse-Ching Chen; Kai-Lin Chiu; Cheng-Rong Hsing; Li-Yu Wang; Chia-Min Yang; Chih-Wen Pao; Chi-Liang Chen (Chemical Engineering Journal, 2025)

Using Gaussian Mixture Model Clustering for the Automated Segmentation of Cerebral Arteriovenous Malformations in Magnetic Resonance Images - Ting-Yu Lin; Cheng‑Chia Lee; Yu-Wei Chen; Hsiu-Mei Wu; Ching-Jen Chen; Huai-Che Yang; Syu-Jyun Peng (Journal of Medical and Biological Engineering, 2025)

A Finite Element Analysis Comparing an Additive Manufacturing Lattice-Structured PEEK Implant to a Commercial Ball-and-Socket Design for Cervical Total Disc Replacement - Ming-Kai Hsieh; Fu-Cheng Kao; Yun-Da Li; De-Mei Lee; Hui Jin; Ching-Lung Tai; Tsung-Ting Tsai; Po-Liang Lai; Weng-Pin Chen (Journal of Medical and Biological Engineering, 2025)
Purpose Cervical total disc replacement (TDR) is commonly performed to treat degenerative cervical spondylosis, but it often faces challenges such as implant wear and migration. This study aimed to develop and evaluate a novel 3D-printed TDR featuring a titanium endplate and a lattice-structured poly-ether-ether-ketone (PEEK) design. The primary objective was to replicate the natural motion of the cervical disc while addressing complications associated with conventional TDRs. Methods The novel implant was created using additive manufacturing techniques, incorporating three lattice-structured PEEK designs (Cross, Octet, and Ventiles) for the nucleus pulposus and annulus fibrosus components. A finite element analysis was conducted to compare the biomechanical performance of the novel TDR with an intact cervical disc and a commercially available TDR (Baguera®C, Spineart SA, Geneva, Switzerland). Key parameters, including maximal von Mises stresses, range of motion, paths of the instantaneous center of rotation, and facet joint stresses, were evaluated under physiological loads (100 N follower load and 1.5 Nm pure moments). Results The novel 3D-printed TDR maintained structural integrity, with stresses remaining within the yield strength of PEEK. The biomechanical performance closely resembled that of an intact cervical disc, demonstrating similar ranges of motion, instantaneous center of rotation paths, and facet joint stress distributions. Conclusion The findings indicate that the innovative 3D-printed TDR may restore normal cervical spinal kinematics more effectively than existing commercial options, potentially reducing the risk of post-operative facet joint syndrome. Further experimental and clinical studies are recommended to validate these results.

Analysis of serotype distribution and characteristics of nonhemolytic and nonpigmented strains among group B Streptococcus isolates in a southern Taiwan local hospital - Hui-Fang Cheng; Zhe-Yu Kuo; Ching-Chiang Lin; Ho-Feng Chen; Horng-Ren Lo; Huey-Wen Shyu; Yi-Fen Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Enhanced nano-LC-MS for analyzing dansylated oral cancer tissue metabolome dissolved in solvents with high elution strength - Ya-Ju Hsieh; Cheng-Yu Hung; Yi-Ting Chen; Yu-Tsun Lin; Kai-Ping Chang; Wei-Fan Chiang; Chih-Yen Chien; Chih-Ching Wu; Liang Li; Jau-Song Yu; Kun-Yi Chien (Analytica Chimica Acta, 2025)

The Impact of Administrative Districts and Urban Landscape on the Dispersal of Aedes aegypti via Genetic Differentiation - Chin‐Gi Huang; Yi‐Cheng Tseng; Tsung‐Han Yu; Hui‐Ching Cheng; Tsung‐Ju Tsai; Jou‐Hsin Ting; Hsin‐Yi Ho; Ya‐Zhe Lee; Yen‐Chieh Chiu; Yu‐Ting Huang; Ting‐Chun Shih; Hsiang‐Yu Hsiao; et al. (Molecular Ecology, 2025)
Mosquito‐borne diseases affect millions and cause numerous deaths annually. Effective vector control, which hinges on understanding their dispersal, is vital for reducing infection rates. Given the variability in study results, likely due to environmental and human factors, gathering local dispersal data is critical for targeted disease control. To analyse the spread and differentiation of Aedes aegypti in southern Taiwan, we established a dengue vector monitoring network in Southern Taiwan's cities. This network employed GPS‐equipped ovitraps to gather eggs that were subsequently hatched in the laboratory and genotyped using genome‐wide SNP markers. From 168 individuals, we identified 757,238 SNPs for detailed analysis. The estimated effective dispersal distance was 154 m (95% CI: 126–180 m), consistent with prior mark‐release‐recapture (MRR) estimates. We discovered that geographic isolation significantly influences genetic differentiation at larger scales, such as between cities, whereas its correlation with genetic distances is considerably weaker at smaller scales, like within cities. This is likely due to the urban landscape in Taiwan, characterised by narrow roads and densely packed buildings, which facilitates extensive dispersal of Ae. aegypti. In evaluating potential barriers to Ae. aegypti dispersal, we found that roads had no significant impact, whereas administrative districts accounted for 4.8% of the population differentiation ( p −4 ). Surprisingly, this variation aligns with the effects of district‐specific mosquito control measures implemented at the municipal level. These findings highlight the complex interplay between urban landscapes, administrative measures and Ae. aegypti dispersal, emphasising the need for implementing targeted control strategies that consider these local dynamics.

Hepatoprotective effect of MUFA-enriched refined Greenland halibut fin oil to inhibit hepatic fibrosis in carbon tetrachloride-induced mice - Pei-Pei Sun; Yi-Sheng Tseng; Chien-Chia Chen; Ching-Shu Lai; Cheng-Di Dong; Vishal Sharma; Mei-Ling Tsai (Food Bioscience, 2024)

Bio-inspired sustainable electrospun quantum nanostructures for high quality factor enabled face masks and self-powered intelligent theranostics - Loganathan Veeramuthu; Ren-Jie Weng; Wei-Hung Chiang; Archana Pandiyan; Fu-Jie Liu; Fang-Cheng Liang; G. Ranjith Kumar; Hua-Yi Hsu; Yu-Ci Chen; Wen-Yinn Lin; Yao-Chun Tang; Wan-Rong Lin; et al. (Chemical Engineering Journal, 2024)

Effect of a tropical cyclone on the pelagic ecosystem of a continental shelf - Chung‐Chi Chen; Chih‐hao Hsieh; Yu‐Hsin Cheng; Wei‐Jen Huang; Wen‐Chen Chou; Fuh‐Kwo Shiah; Gwo‐Ching Gong; Tzong‐Yueh Chen (Limnology and Oceanography, 2024)
This study aimed to comprehend the effects of Typhoon Maria on the pelagic ecosystem in the southern East China Sea. Shipboard measurements were conducted at eight sampling stations before (2–4 d) and after (3–6 d) the typhoon, which enabled the evaluation of the potential impacts of the typhoon on this pelagic ecosystem, with particular focus on carbon dynamics. Following the typhoon's passage, there was a slight drop in sea surface temperature. The response of the variables to the typhoon, however, exhibited variations at different sampling stations. For further analysis, t ‐tests compared variables, while type II regression assessed the linear correlation between two variables. Overall, during the post‐typhoon period, concentrations of nitrate, chlorophyll a , primary production, bacterial biomass and production, plankton community respiration, and abundance of large phytoplankton (> 2 μ m) and the relative abundance of picophytoplankton among larger‐sized picoeukaryotes were higher compared to the pre‐typhoon period. The mean value of fugacity of CO 2 was similar to or slightly lower than pre‐typhoon period. Although the typhoon‐induced vigorous primary production might have absorbed a significant amount of CO 2 , the decrease in fugacity of CO 2 could have been offset by the plankton community respiration. The findings suggest that the typhoon enhanced physical disturbance and increased water column mixing, which, in turn, augmented nutrient availability and promoted plankton growth in the shallow water column. Overall, this study sheds light on the complex interactions between typhoons and marine ecosystems and highlights the importance of further investigating these phenomena to better understand their ecological implications.

Development of Quantitative Norms for Normal Lung Uptake Based on Three-Dimensional Gallium-67 Single Photon Emission Computed Tomography/Computed Tomography - Tzyy-Ling Chuang; Wei-Lin Li; Yu-Ching Hs; Jyh-Cheng Chen; Yuh-Feng Wang (Journal of Medical and Biological Engineering, 2024)
Purpose Gallium-67 (Ga-67) lung scans assess alveolitis and interstitial lung disease, with Ga-67 accumulation correlating with inflammation intensity as seen in lung biopsy sections. Both semi-quantitative and quantitative methods have been used, with the latter providing an inflammatory activity index linked to lung lavage and histopathological scores. However, differing reference points result in varying outcomes. This study aimed to establish standard Ga-67 index parameters using semi-quantitative analysis and a linear regression model based on planar and SPECT/CT images. Methods Twenty subjects without lung disease received a 5–6 mCi Ga-67 injection via the ankle. Both planar and SPECT/CT images were analyzed, with semi-quantitative values assessed using GraphPad Prism 9.5.1. Results Compared to planar images, SPECT/CT acquisitions for the lung-to-arm uptake ratio proved the most reliable indicator for assessing lung inflammation. Increased lung Ga-67 uptake was defined as greater than 2 standard deviations from the average Ga-67 uptake for healthy subjects. The normal range was 0.065 ± 0.049 for the right side and 0.076 ± 0.070 for the left side. Conclusion Lung-to-arm ratios in SPECT/CT images are more accurate than those in planar images. This method should be adopted as a standard clinical practice, providing more reliable diagnostic information and improving patient management. Future studies should compare patients without lung disease to those with lung disease to determine the diagnostic benefit of these norms.

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Classification of aged batteries based on capacity and/or resistance through machine learning models with aging features as input: A comparative study - Yi-Cheng Wang; Kuo-Ching Chen (Journal of Cleaner Production, 2024)

Modelling the distribution of fish habitat type and habitat diversity in natural rivers - Hsuan-Ju Hung; Wei-Cheng Lo; Ching-Nuo Chen; Chih-Heng Tsai (Journal for Nature Conservation, 2024)

Surface engineering of the lightweight aggregates derived from the dredged harbor sediment for green fertilizer utilization - TsingHai Wang; ZiYing Lu; ChiaYu You; Wei-Fan Kuan; Ching-Lung Chen; Yee Cheng Lim; Chiu-Wen Chen; Cheng-Di Dong (Process Safety and Environmental Protection, 2024)

Investigation of space group effects of High-Voltage spinel LiNi0.5Mn1.5O4: Unveiling the influences of fluorinate benzimidazole salt additive - Chusnul Khotimah; Rio Akbar Yuwono; Fu-Ming Wang; Chun-Chen Yang; Nae-Lih Wu; Citra Deliana Dewi Sundari; Arif Cahyo Imawan; Ching-Kai Chang; Ping-Hsuan Hsu; Pin-Cheng Huang; Guan-Yi Liu; Yi-De Tsai; et al. (Chemical Engineering Journal, 2024)

Surface ligand engineering of perovskite quantum dots for n-type and stretchable photosynaptic transistor with an ultralow energy consumption - Wei-Cheng Chen; Yan-Cheng Lin; Zih-Syuan Syu; Ya-Shuan Wu; Kai-Wei Lin; Cheng-Liang Liu; Chi-Ching Kuo; Wen-Chang Chen (Chemical Engineering Journal, 2024)

Predicting ischemic stroke patients’ prognosis changes using machine learning in a nationwide stroke registry - Ching-Heng Lin; Yi-An Chen; Jiann-Shing Jeng; Yu Sun; Cheng-Yu Wei; Po-Yen Yeh; Wei-Lun Chang; Yang C. Fann; Kai-Cheng Hsu; Jiunn-Tay Lee (Medical & Biological Engineering & Computing, 2024)
Accurately predicting the prognosis of ischemic stroke patients after discharge is crucial for physicians to plan for long-term health care. Although previous studies have demonstrated that machine learning (ML) shows reasonably accurate stroke outcome predictions with limited datasets, to identify specific clinical features associated with prognosis changes after stroke that could aid physicians and patients in devising improved recovery care plans have been challenging. This study aimed to overcome these gaps by utilizing a large national stroke registry database to assess various prediction models that estimate how patients’ prognosis changes over time with associated clinical factors. To properly evaluate the best predictive approaches currently available and avoid prejudice, this study employed three different prognosis prediction models including a statistical logistic regression model, commonly used clinical-based scores, and a latest high-performance ML-based XGBoost model. The study revealed that the XGBoost model outperformed other two traditional models, achieving an AUROC of 0.929 in predicting the prognosis changes of stroke patients followed for 3 months. In addition, the XGBoost model maintained remarkably high precision even when using only selected 20 most relevant clinical features compared to full clinical datasets used in the study. These selected features closely correlated with significant changes in clinical outcomes for stroke patients and showed to be effective for predicting prognosis changes after discharge, allowing physicians to make optimal decisions regarding their patients’ recovery. Graphical Abstract

Assessment of PM2.5-associated mortality burden among the elderly: Insights into demographic, socio-economic, and geographic factors - Ayushi Sharma; Hsi-yu Hsiao; Jia-Yi Liu; Shih-Chun Candice Lung; Huey-Jen Su; Ching-Fen Shen; Nai-Tzu Chen; Pei-Chih Wu; Cheng-Yu Lin; Sheng-Fu Liang; Tain-Junn Cheng; Ta-Chien Chan; et al. (Air Quality, Atmosphere & Health, 2024)

Enhancing methane formation in carbon dioxide hydrogenation on nickel clusters with zirconium additives: Exploring active sites, reaction pathways, and catalytic mechanisms - Ching-Shiun Chen; Tse-Ching Chen; Jia Huang Wu; Hung-Chi Wu; Chia-Min Yang; Tsung-Cheng Yang; Chih-Wen Pao (Chemical Engineering Journal, 2024)

Examining arterial pulsation to identify and risk-stratify heart failure subjects with deep neural network - Chieh-Chun Huang; Shih-Hsien Sung; Wei-Ting Wang; Yin-Yuan Su; Chi-Jung Huang; Tzu-Yu Chu; Shao-Yuan Chuang; Chern-En Chiang; Chen-Huan Chen; Chen-Ching Lin; Hao-Min Cheng (Physical and Engineering Sciences in Medicine, 2024)
Hemodynamic parameters derived from pulse wave analysis have been shown to predict long-term outcomes in patients with heart failure (HF). Here we aimed to develop a deep-learning based algorithm that incorporates pressure waveforms for the identification and risk stratification of patients with HF. The first study, with a case–control study design to address data imbalance issue, included 431 subjects with HF exhibiting typical symptoms and 1545 control participants with no history of HF (non-HF). Carotid pressure waveforms were obtained from all the participants using applanation tonometry. The HF score, representing the probability of HF, was derived from a one-dimensional deep neural network (DNN) model trained with characteristics of the normalized carotid pressure waveform. In the second study of HF patients, we constructed a Cox regression model with 83 candidate clinical variables along with the HF score to predict the risk of all-cause mortality along with rehospitalization. To identify subjects using the HF score, the sensitivity, specificity, accuracy, F1 score, and area under receiver operating characteristic curve were 0.867, 0.851, 0.874, 0.878, and 0.93, respectively, from the hold-out cross-validation of the DNN, which was better than other machine learning models, including logistic regression, support vector machine, and random forest. With a median follow-up of 5.8 years, the multivariable Cox model using the HF score and other clinical variables outperformed the other HF risk prediction models with concordance index of 0.71, in which only the HF score and five clinical variables were independent significant predictors (p < 0.05), including age, history of percutaneous coronary intervention, concentration of sodium in the emergency room, N -terminal pro-brain natriuretic peptide, and hemoglobin. Our study demonstrated the diagnostic and prognostic utility of arterial waveforms in subjects with HF using a DNN model. Pulse wave contains valuable information that can benefit the clinical care of patients with HF.

An Automatic Approach of Video-Based Landmark Detection and Movement Analysis for Assessing Symptoms of Bradykinesia in Parkinson’s Disease - Ching-Fang Chien; Chen-Sen Ouyang; Yi-Hung Chiu; Lung-Chang Lin; Rei-Cheng Yang; Yang-Pei Chang; San-Yuan Wang; Li-Min Liou (Journal of Medical and Biological Engineering, 2024)

Quantifying payloads of antibody‒drug conjugates using a postcolumn infused-internal standard strategy with LC‒MS - Chih-Ning Cheng; Hsiao-Wei Liao; Ching-Hung Lin; Wen-Chi Chang; I-Chun Chen; Yen-Shen Lu; Ching-Hua Kuo (Analytica Chimica Acta, 2024)

Exposure estimates of PM2.5 using the land-use regression with machine learning and microenvironmental exposure models for elders: Validation and comparison - Chin-Yu Hsu; Wei-Ting Hsu; Ching-Yi Mou; Pei-Yi Wong; Chih-Da Wu; Yu-Cheng Chen (Atmospheric Environment, 2024)

Green cost performance measure of China’s thermal power industry: evidence from Chinese 30 provinces - Xiang Chen; Jiayu Zhang; Chih-Yu Yang; Ching-Cheng Lu; Jun Wang (Environment, Development and Sustainability, 2024)

Property rights arrangement and stakeholder networks hindering floating photovoltaics: A case of private open-access ponds in Taiwan - Yi-Chieh Chen; Kenneth Bicol Dy; Ching-Cheng Chang; Shih-Hsun Hsu (Energy Policy, 2024)

A longitudinal study on the change in sleep across three waves of the COVID-19 outbreaks in Hong Kong - Denise Shuk Ting Cheung; Branda Yee-Man Yu; Simon Ching Lam; Doris Yin Ping Leung; Ka-Fai Chung; Fiona Yan-Yee Ho; Shu-Cheng Chen; Wing-Fai Yeung (Sleep and Biological Rhythms, 2024)

Evaluating the toxic mechanism of 1,2-diacetylbenzene in neural cells/tissues: The favorable impact of silibinin - Li-Yu Fay; Jun-Yi Chien; Ching-Feng Weng; Huai-Sheng Kuo; Dann-Ying Liou; Wei-Hao Weng; Chi-Hung Lin; Ya-Tzu Chen; Wen-Hung Huang; Wen-Cheng Huang; May-Jywan Tsai; Henrich Cheng (NeuroToxicology, 2023)

A crosslinked waterborne poly(vinyl acetate) for greenhouse gas fixation with improved elastomeric properties, shape-memory ability, and recyclability - Yen-Chuan Chen; Ying-Chi Huang; Yi-Hua Huang; Ying-Feng Lin; Ho-Ching Huang; Ru-Jong Jeng; Yu-Wei Cheng; Chien-Hsin Wu (Journal of Environmental Chemical Engineering, 2023)

Generation of artificial rainfall events for flood risk assessment in Taiwan - Wen-Ko Hsu; Pei-Chiung Huang; Ching-Cheng Chang; Wei-Ling Chiang; Dung-Jiang Chiou; Cheng-Wu Chen (Natural Hazards, 2023)

Tandem surface engineering of graphene quantum dot-assisted fluorinated NiFe Prussian blue analogue for electrocatalytic oxygen evolution reaction - Angelina Melanita Tarigan; Sofiannisa Aulia; Mia Rinawati; Ling-Yu Chang; Yao-Sheng Cheng; Ching-Cheng Chang; Wei-Hsiang Huang; Jeng-Lung Chen; Heru Setyawan; Min-Hsin Yeh (Chemical Engineering Journal, 2023)

Severity of Liver Cirrhosis Evaluated by Digital Subtraction Angiography Using Quantitative Color-Coding Analysis Before Transarterial Embolization - Lung-Hui Giiang; Chang-Hsien Liu; Chih-Yung Yu; Te-Pao Lin; Hsiang-Cheng Chen; Chun-Jung Juan; Yu-Ching Chou (Journal of Medical and Biological Engineering, 2023)

Parameter correlation study on two new analytical solutions for radially divergent tracer tests in two-zone confined aquifers with vertical dispersion effect - Chen Wang; Ching-Sheng Huang; Chenchen Tong; Cheng-Haw Lee (Advances in Water Resources, 2023)

Ethanol production using the whole solid-state fermented sugarcane bagasse cultivated by Trichoderma reesei RUT-C30 supplemented with commercial cellulase - Ching An Lin; Cheng Cheng; Li Wei Chen; C. Will Chen; Kow Jen Duan (Biocatalysis and Agricultural Biotechnology, 2023)

Commentary: Evaluating stock status of 16 commercial fish species in the coastal and offshore waters of Taiwan using the CMSY and BSM methods - Ting-Chun Kuo; Nan-Jay Su; Ching-Chun Cheng; Kwang-Ming Liu; Chih-Shin Chen; Hsueh-Jung Lu; Ming-An Lee (Frontiers in Marine Science, 2023)

Long-term DEHP/MEHP exposure promotes colorectal cancer stemness associated with glycosylation alterations - Pei-Chun Shih; Hsin-Pao Chen; Ching-Cheng Hsu; Chung-Hsien Lin; Chou-Yuan Ko; Chao-Wen Hsueh; Cheng-Yi Huang; Tian-Huei Chu; Cheng-Chun Wu; Yu-Cheng Ho; Ngoc Uyen Nhi Nguyen; Shih-Chung Huang; et al. (Environmental Pollution, 2023)

Recent development of sustainable self-healable electronic skin applications, a review with insight - Jean-Sébastien Benas; Fang-Cheng Liang; Manikandan Venkatesan; Zhen-Li Yan; Wei-Cheng Chen; Su-Ting Han; Ye Zhou; Chi-Ching Kuo (Chemical Engineering Journal, 2023)

Predicting survival after radiosurgery in patients with lung cancer brain metastases using deep learning of radiomics and EGFR status - Chien-Yi Liao; Cheng-Chia Lee; Huai-Che Yang; Ching-Jen Chen; Wen-Yuh Chung; Hsiu-Mei Wu; Wan-Yuo Guo; Ren-Shyan Liu; Chia-Feng Lu (Physical and Engineering Sciences in Medicine, 2023)

Improvement of enzymatic cross-linking of ovalbumin and ovotransferrin induced by transglutaminase with heat and reducing agent pretreatment - Chun-Chi Chen; Ming-Ching Kao; Chao-Jung Chen; Cheng-Hsun Jao; Jung-Feng Hsieh (Food Chemistry, 2023)

Toward sustainable inland aquaculture: Coastal subsidence monitoring in Taiwan - Wei-Chia Hung; Cheinway Hwang; Luigi Tosi; Shao-Hung Lin; Pei-Ching Tsai; Yi-An Chen; Wei-Ji Wang; En-Cheng Li; Sihao Ge (Remote Sensing Applications: Society and Environment, 2023)

Modelling chloroform in indoor swimming pool air and water: the influences of internal air circulation and occupants - Hui-Tsung Hsu; Ming-Jen Chen; Kuang-Chung Tsai; Li-Jen Huang; Ching-Ho Lin; Chin-Hsing Lai; Li-Hsin Cheng (Environmental Science and Pollution Research, 2023)

Nitrogen-phosphorous co-doped palladium electrocatalyst for glycerol electro-oxidation reaction (GEOR): An efficient system for mesoxalic acid and dihydroxyacetone production - Muhammad Sheraz Ahmad; Kim Hoong Ng; Ching-Lung Chen; Faryal Kabir; Thongthai Witoon; Ta Yeong Wu; Chin Kui Cheng (Fuel, 2023)

Two new chromones and a new coumarin from the fruit of Cnidium monnieri (L.) Cusson - Hui-Chi Huang; Chun-Hsiang Lin; Ching-Chuan Kuo; Ming-Der Wu; Ming-Jen Cheng; Jih-Jung Chen; Che-Yi Chao; Guan-Jhong Huang; Yueh-Hsiung Kuo (Natural Product Research, 2023)

Bioremediation potential of cadmium by recombinant Escherichia coli surface expressing metallothionein MTT5 from Tetrahymena thermophila - Che-Wei Lu; Hsin-Cheng Ho; Chao-Ling Yao; Tsung-Yu Tseng; Chih-Ming Kao; Ssu-Ching Chen (Chemosphere, 2023)

Development of the dried blood spot preparation protocol for comprehensive evaluation of the hematocrit effect - Chih-Ning Cheng; Yu-Fong Peng; Ju-Yu Chen; Guan-Yuan Chen; Te-I Weng; Ching-Hua Kuo (Analytica Chimica Acta, 2023)

Prediction of Groundwater Quality Using Seven Types of First-Order Univariate Grey Model in the Chishan Basin, Taiwan - Tzu-Yi Pai; Ray-Shyan Wu; Ching-Ho Chen; Huang-Mu Lo; Terng-Jou Wan; Min-Hsin Liu; Wei-Cheng Chen; Yi-Ping Lin; Chun-Tse Hsu (Water, Air, & Soil Pollution, 2022)

QTL analyses of soybean root system architecture revealed genetic relationships with shoot-related traits - Zhili Wang; Cheng Huang; Yongchao Niu; Wai-Shing Yung; Zhixia Xiao; Fuk-Ling Wong; Mingkun Huang; Xin Wang; Chun-Kuen Man; Ching-Ching Sze; Ailin Liu; Qianwen Wang; et al. (Theoretical and Applied Genetics, 2022)

Lactobacillus plantarum PS128 Promotes Intestinal Motility, Mucin Production, and Serotonin Signaling in Mice - Chih-Ming Chen; Chien-Chen Wu; Chin-Lin Huang; Min-Yu Chang; Shih-Hsuan Cheng; Ching-Ting Lin; Ying-Chieh Tsai (Probiotics and Antimicrobial Proteins, 2022)
Lactobacillus plantarum PS128 has been reported as a psychobiotic to improve mental health through the gut–brain axis in experimental animal models. To explore its mechanism of action in the gut, this study aimed to analyze the effects of L. plantarum PS128 ingestion on naïve and loperamide (Lop)-induced constipation mice. We found that, in the two mouse models, the weight, number, and water content of feces in the L. plantarum PS128 group were higher than those in the vehicle control group. Histological observation revealed that L. plantarum PS128 increased the level of colonic mucins including the major mucin MUC2. In addition, the charcoal meal test showed that L. plantarum PS128 significantly increased the small intestine transit in naïve mice, but not in the Lop-treated mice. Since intestinal serotonin has been found to modulate motility, we further analyzed the expression of genes related to serotonin signal transduction in the small intestine of naïve mice. The results showed that L. plantarum PS128 significantly altered the expression levels of Tph1 , Chga , Slc6a4 , and Htr4 , but did not affect the expression levels of Tph2 , Htr3a , and Maoa . Furthermore, immunohistochemistry revealed that L. plantarum PS128 significantly increased the number of serotonin-containing intestinal cells in mice. Taken together, our results suggest that L. plantarum PS128 could promote intestinal motility, mucin production, and serotonin signal transduction, leading to a laxative effect in mice.

Using DeepLab v3 + -based semantic segmentation to evaluate platelet activation - Tsung-Chen Kuo; Ting-Wei Cheng; Ching-Kai Lin; Ming-Che Chang; Kuang-Yao Cheng; Yun-Chien Cheng (Medical & Biological Engineering & Computing, 2022)

TREM-2 mediates dendritic cell–induced NO to suppress Th17 activation and ameliorate chronic kidney diseases - Ching-Cheng Lin; Ti-Yung Chang; Yong-Chen Lu; Yun-Syuan Wu; Wei Huang; Wei-Chi Lo; Guan-Fu Liu; Wei-Chan Hsu; Pamela S. Ohashi; Tak W. Mak; Jong-Ling Fuh; Hui-Chen Chen; et al. (Journal of Molecular Medicine, 2022)

Geographic distance, sedimentation, and substrate shape cryptic crustose coralline algal assemblages in the world’s largest subtropical intertidal algal reef - Shing Hei Zhan; Ling Chen; Chen‐Pan Liao; Wun‐Ruei Chang; Cheng‐Chin Li; Guang‐You Tang; Ching‐Yu Liou; Wei‐Lung Wang; Shih‐Wei Wang; Shao‐Lun Liu (Molecular Ecology, 2022)
Algal reefs, concreted by crustose coralline algae (CCA), are the main biotic reefs in temperate waters but rare in the subtropics and tropics. The world's largest known intertidal algal reef in the subtropics is the Taoyuan Algal Reef (TAR) located in the northwestern coast of Taiwan. The biodiversity and ecology of the TAR are scarcely explored, and now the reef is imperiled by industrialization. Here, we document cryptic species of CCA in Taiwan, particularly the TAR, by sequencing the psb A genes of over 1800 specimens collected across Taiwan. We also examine the ecological background of the TAR by surveying its benthic composition and measuring its environmental parameters. Our data reveal that the TAR harbours a high diversity of cryptic CCA species (27 molecular operational taxonomic units, or mOTUs), many of which are potentially new to science (18 mOTUs) and/or endemic to the TAR (9 mOTUs). Comparing the CCA species inventory of the TAR with the rest of Taiwan shows that the TAR represents a unique hotspot of CCA taxa in the waters of Taiwan. Our analyses show that variation in the CCA assemblages in the TAR is associated with geographic distance, sedimentation, and substrate type (for example, reef vs. hermit crab shell), suggesting that dispersal limitation and contemporary environmental selection shape the CCA assemblages in the TAR. The data from this study can inform the monitoring of human impacts on the health of the TAR and contribute to our understanding of the ecological processes underlying algal reef development.

Interleukin-6 transiently promotes proliferation of osteoclast precursors and stimulates the production of inflammatory mediators - Peng-Yuan Chang; Hung-Kang Wu; Yu-Hsu Chen; Yu-Pao Hsu; Ming-Te Cheng; Ching-Hsiao Yu; Shau-Kwaun Chen (Molecular Biology Reports, 2022)

A Unique Diel Pattern in Carbonate Chemistry in the Seagrass Meadows of Dongsha Island: The Enhancement of Metabolic Carbonate Dissolution in a Semienclosed Lagoon - Wen-Chen Chou; Lan-Feng Fan; Chang-Chang Yang; Ying-Hsuan Chen; Chin-Chang Hung; Wei-Jen Huang; Yung-Yen Shih; Keryea Soong; Hsiao-Chun Tseng; Gwo-Ching Gong; Hung-Yu Chen; Cheng-Kuan Su (Frontiers in Marine Science, 2021)
In contrast to other seagrass meadows where seawater carbonate chemistry generally shows strong diel variations with higher pH but lower partial pressure of CO 2 ( p CO 2 ) during the daytime and lower pH but higher p CO 2 during nighttime due to the alternation in photosynthesis and respiration, the seagrass meadows of the inner lagoon (IL) on Dongsha Island had a unique diel pattern with extremely high pH and low p CO 2 across a diel cycle. We suggest that this distinct diel pattern in pH and p CO 2 could be associated with the enhancement of total alkalinity (TA) production coupled to carbonate sediment dissolution in a semienclosed lagoon. The confinement of the IL may hamper water exchange and seagrass detritus export to the adjacent open ocean, which may result in higher organic matter loading to the sediments, and longer residence time of the water in the IL, accompanied by microbial respiration (both aerobic and anaerobic) that may reduce carbonate saturation level to drive carbonate dissolution and thus TA elevation, thereby forming such a unique diel pattern in carbonate chemistry. This finding further highlights the importance of considering TA production through metabolic carbonate dissolution when evaluating the potential of coastal blue carbon ecosystems to buffer ocean acidification and to absorb atmospheric CO 2 , in particular in a semienclosed setting.

A Comparative Analysis of Slack-Based Green Total Factor Productivity in China: a Directional Distance Function - Xuping Zhang; Xiang Chen; Ching-Cheng Lu; Fu-Yueh Cheng (Water, Air, & Soil Pollution, 2021)

The use of multi-pronged screening strategy to understand the epidemiology of carbapenemase-producing Enterobacteriaceae in Hong Kong: transition from epidemic to endemic setting - Shuk- Ching Wong; Veronica Wing- Man Chan; Germaine Kit-Ming Lam; Christine Ho-Yan AuYeung; Elaine Yin-Ling Leung; Simon Yung-Chun So; Jonathan Hon-Kwan Chen; Siddharth Sridhar; Anthony Raymond Tam; Ivan Fan-Ngai Hung; Pak- Leung Ho; Kwok- Yung Yuen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Viable and Heat-Killed Probiotic Strains Improve Oral Immunity by Elevating the IgA Concentration in the Oral Mucosa - Wen-Yang Lin; Yi-Wei Kuo; Ching-Wei Chen; Yu-Fen Huang; Chen-Hung Hsu; Jia-Hung Lin; Cheng-Ruei Liu; Jui-Fen Chen; Ko-Chiang Hsia; Hsieh-Hsun Ho (Current Microbiology, 2021)
Oral-nasal mucosal immunity plays a crucial role in protecting the body against bacterial and viral invasion. Safe probiotic products have been used to enhance human immunity and oral health. In this study, we verified the beneficial effects of mixed viable probiotic tablets, consisting of Lactobacillus salivarius subsp. salicinius AP-32, Bifidobacterium animalis subsp. lactis CP-9, and Lactobacillus paracasei ET-66, and heat-killed probiotic tablets, consisting of L. salivarius subsp. salicinius AP-32 and L. paracasei ET-66, on oral immunity among 45 healthy participants. Participants were randomly divided into viable probiotic, heat-killed probiotic, and placebo groups. The administration of treatment lasted for 4 weeks. Saliva samples were collected at Weeks 0, 2, 4, and 6, and Lactobacillus , Bifidobacterium and Streptococcus mutans populations and IgA concentration were measured. IgA concentrations, levels of TGF-beta and IL-10 in PBMCs cells were quantified by ELISA method. Results showed that salivary IgA levels were significantly increased on administration of both the viable (119.30 ± 12.63%, *** P < 0.001) and heat-killed (116.78 ± 12.28%, *** P < 0.001) probiotics for 4 weeks. Among three probiotic strains, AP-32 would effectively increase the levels of TGF-beta and IL-10 in PBMCs. The oral pathogen Streptococcus mutans was significantly reduced on viable probiotic tablet administration (49.60 ± 31.01%, *** P < 0.001). The in vitro antibacterial test confirmed that viable probiotics effectively limited the survival rate of oral pathogens. Thus, this clinical pilot study demonstrated that oral probiotic tablets both in viable form or heat-killed form could exert beneficial effects on oral immunity via IL-10, TGB-beta mediated IgA secretion. The effective dosage of viable probiotic content in the oral tablet was 10 9 CFUs/g and the heat-killed oral tablet was 1 × 10 10 cells/g.

Effect of selected sampling media, flow rate, and time on the sampling efficiency of a liquid impinger packed with glass beads for the collection of airborne viruses - Yen-Chi Chen; I-Jen Wang; Chih-Ching Cheng; Yu-Chiao Wu; Chun-Hsuan Bai; Kuo-Pin Yu (Aerobiologia, 2021)

Fibroblast Growth Factor 9 Stimulates Neuronal Length Through NF-kB Signaling in Striatal Cell Huntington’s Disease Models - Issa Olakunle Yusuf; Hsiu-Mei Chen; Pei-Hsun Cheng; Chih-Yi Chang; Shaw-Jenq Tsai; Jih-Ing Chuang; Chia-Ching Wu; Bu-Miin Huang; H. Sunny Sun; Chuan-Mu Chen; Shang-Hsun Yang (Molecular Neurobiology, 2021)

Carbon monoxide-triggered health effects: the important role of the inflammasome and its possible crosstalk with autophagy and exosomes - Rong-Jane Chen; Yu-Hsuan Lee; Tzu-Hao Chen; Yu-Ying Chen; Ya-Ling Yeh; Ching-Ping Chang; Chien-Cheng Huang; How-Ran Guo; Ying-Jan Wang (Archives of Toxicology, 2021)

Risk of incident gastroesophageal reflux disease (GERD) in patients with sleep disorders: a population-based cohort study - Yu-Hsien Cheng; Tao-Hsin Tung; Pei-En Chen; Ching-Yao Tsai (Sleep and Biological Rhythms, 2021)

Doxorubicin metabolism moderately attributes to putative toxicity in prodigiosin/doxorubicin synergism in vitro cells - Shian-Ren Lin; Chun-Shu Lin; Ching-Cheng Chen; Feng-Jen Tseng; Tsung-Jui Wu; Lebin Weng; Ching-Feng Weng (Molecular and Cellular Biochemistry, 2020)
Doxorubicin (Dox) is a widely neoplasm chemotherapeutic drug with high incidences of cardiotoxicity. Prodigiosin (PG), a red bacterial pigment from Serratia marcescens , has been demonstrated to potentiate Dox’s cytotoxicity against oral squamous cell carcinoma cells through elevating Dox influx and identified as a Dox enhancer via PG-induced autophagy; however, toxicity of normal cell remains unclear. This study is conducted to evaluate putative cytotoxicity features of PG/Dox synergism in the liver, kidney, and heart cells and further elucidate whether PG augmented Dox’s effect via modulating Dox metabolism in normal cells. Murine hepatocytes FL83B, cardio-myoblast h9c2, and human kidney epithelial cells HK-2 were sequentially treated with PG and Dox by measuring cell viability, cell death characteristics, oxidative stress, Dox flux, and Dox metabolism. PG could slightly significant increase Dox cytotoxicity in all tested normal cells whose toxic alteration was less than that of oral squamous carcinoma cells. The augmentation of Dox cytotoxicity might be attributed to the increase of Dox-mediated ROS accumulation that might cause slight reduction of Dox influx and reduction of Dox metabolism. It was noteworthy to notice that sustained cytotoxicity appeared in normal cells after PG and Dox were removed. Taken together, moderately metabolic reduction of Dox might be ascribed to the mechanism of increase Dox cytotoxicity in PG-induced normal cells; nevertheless, the determination of PG/Dox dose with sustained cytotoxicity in normal cells needs to be comprehensively considered.

New gravimetric-only and hybrid geoid models of Taiwan for height modernisation, cross-island datum connection and airborne LiDAR mapping - Cheinway Hwang; Hung-Jui Hsu; W. E. Featherstone; Ching-Chung Cheng; Ming Yang; Wenhsuan Huang; Chong-You Wang; Jiu-Fu Huang; Kwo-Hwa Chen; Chi-Hsun Huang; Hechin Chen; Wen-Yi Su (Journal of Geodesy, 2020)

Two new diprenylated flavanones from Derris laxiflora Benth - Hui-Chi Huang; Shih-Chang Chien; Ching-Chuan Kuo; Ming-Der Wu; Ming-Jen Cheng; Jih-Jung Chen; Hsi-Lin Chiu; Yueh-Hsiung Kuo (Natural Product Research, 2020)

New land use regression model to estimate atmospheric temperature and heat island intensity in Taiwan - Chin-Yu Hsu; Uen-Ching Ng; Chiao-Ying Chen; Yu-Cheng Chen; Mu-Jean Chen; Nai-Tzu Chen; Shih-Chun Candice Lung; Huey-Jen Su; Chih-Da Wu (Theoretical and Applied Climatology, 2020)

Statistical Analysis on Heart Rate Variability for Graded Cardiopulmonary Groups with Different Exercise Intensities - Ching-Kun Chen; Shyan-Lung Lin; Cheng-Yi Huang; Tasi-Chu Wang; Ting-Yen Yao; Chieh-Liang Wu (Journal of Medical and Biological Engineering, 2020)

Comparative Study of Regulations of Devices for Aesthetic Purposes: US, European Union, China, and Taiwan - Mei-Fen Chen; Cheng-Lun Tsai; Yung-Hsin Chen; Cheng-Ning Wu; Ching Chou; Chia-Hung Chien; Pei-Weng Tu; Tsair Kao; Kang-Ping Lin (Journal of Medical and Biological Engineering, 2020)

Pulse Oximetry Monitor Feasible for Early Screening of Obstructive Sleep Apnea (OSA) - Huei-Chen Lin; Chien-Ling Su; Jun-Hui Ong; kun-ling Tsai; Yu-Wen Chen; Cheng-Yu Lin; Ling-Ling Chiang; Ching-Hsia Hung (Journal of Medical and Biological Engineering, 2020)

Urinary biomarkers of polycyclic aromatic hydrocarbons and the association with hearing threshold shifts in the United States adults - Cheng-Wai Chou; Yuan-Yuei Chen; Chung-Ching Wang; Tung-Wei Kao; Chen-Jung Wu; Ying-Jen Chen; Yi-Chao Zhou; Wei-Liang Chen (Environmental Science and Pollution Research, 2020)

A multidecadal change analysis for irrigation ponds in Taoyuan, Taiwan, using multisource data - Yen-Ching Chen; Wei-Chun Lin; Lin-Hsuan Hsiao; Ke-Sheng Cheng (Paddy and Water Environment, 2020)

In vitro activities of imipenem, vancomycin, and rifampicin against clinical Elizabethkingia species producing BlaB and GOB metallo-beta-lactamases - Tein-Yao Chang; Hsing-Yu Chen; Yu-Ching Chou; Yun-Hsiang Cheng; Jun-Ren Sun (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

An integrative assessment to determine the sediment toxicity of Kaohsiung Harbor in Taiwan: combining chemical analysis and cytotoxicity assay - Yun-Ru Ju; Chih-Feng Chen; Chiu-Wen Chen; Mei-Ling Tsai; Jia-Ching Wu; Cheng-Di Dong (Environmental Science and Pollution Research, 2019)

Blood and seminal plasma mercury levels and predatory fish intake in relation to low semen quality - Chin-En Ai; Ching-Jen Li; Ming-Chien Tsou; Jun-Lin Chen; Hsing-Cheng Hsi; Ling-Chu Chien (Environmental Science and Pollution Research, 2019)

PARK14 (D331Y) PLA2G6 Causes Early-Onset Degeneration of Substantia Nigra Dopaminergic Neurons by Inducing Mitochondrial Dysfunction, ER Stress, Mitophagy Impairment and Transcriptional Dysregulation in a Knockin Mouse Model - Ching-Chi Chiu; Chin-Song Lu; Yi-Hsin Weng; Ying-Ling Chen; Ying-Zu Huang; Rou-Shayn Chen; Yi-Chuan Cheng; Yin-Cheng Huang; Yu-Chuan Liu; Szu-Chia Lai; Kun-Jun Lin; Yan-Wei Lin; et al. (Molecular Neurobiology, 2019)

Magnesium sulfate inhibits binding of lipopolysaccharide to THP-1 cells by reducing expression of cluster of differentiation 14 - Ya-Ying Chang; Tzu-Yu Lin; Ming-Chang Kao; Tsung-Ying Chen; Ching-Feng Cheng; Chih-Shung Wong; Chun-Jen Huang (Inflammopharmacology, 2019)

Whole-genome sequencing data-based modeling for the investigation of an outbreak of community-associated methicillin-resistant Staphylococcus aureus in a neonatal intensive care unit in Hong Kong - Vincent C. C. Cheng; Shuk-Ching Wong; Huiluo Cao; Jonathan H. K. Chen; Simon Y. C. So; Sally C. Y. Wong; Siddharth Sridhar; Kwok-Yung Yuen; Pak-Leung Ho (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Spatial dynamic assessment of health risks for urban river cruises - Cheng-Shin Jang; Ching-Ping Liang; Shih-Kai Chen (Environmental Monitoring and Assessment, 2019)

Adenosine Augmentation Evoked by an ENT1 Inhibitor Improves Memory Impairment and Neuronal Plasticity in the APP/PS1 Mouse Model of Alzheimer’s Disease - Chia-Chia Lee; Ching-Pang Chang; Chun-Jung Lin; Hsing-Lin Lai; Yu-Han Kao; Sin-Jhong Cheng; Hui-Mei Chen; Yu-Ping Liao; Emilie Faivre; Luc Buée; David Blum; Jim-Min Fang; et al. (Molecular Neurobiology, 2018)

Exercise Rehabilitation Attenuates Cognitive Deficits in Rats with Traumatic Brain Injury by Stimulating the Cerebral HSP20/BDNF/TrkB Signalling Axis - Willy Chou; Yu-Fan Liu; Cheng-Hsien Lin; Mao-Tsun Lin; Chi-Chun Chen; Wen-Pin Liu; Ching-Ping Chang; Chung-Ching Chio (Molecular Neurobiology, 2018)

Web-Based Experience Sharing Platform on Medical Device Incidents for Clinical Engineers in Hospitals - Mei-Fen Chen; Cheng-Lun Tsai; Yung-Hsin Chen; Yu-Wen Huang; Cheng-Ning Wu; Ching Chou; Chia-Hung Chien; Pei-Weng Tu; Tsair Kao; Kang-Ping Lin (Journal of Medical and Biological Engineering, 2018)

Effects of normoxic and hypoxic exercise training on the bactericidal capacity and subsequent apoptosis of neutrophils in sedentary men - Yi-Ching Chen; Wan-Yu Chou; Tieh-Cheng Fu; Jong-Shyan Wang (European Journal of Applied Physiology, 2018)

Lamelloplasts and minichloroplasts in Begoniaceae: iridescence and photosynthetic functioning - Shang-Hung Pao; Ping-Yun Tsai; Ching-I Peng; Pei-Ju Chen; Chi-Chu Tsai; En-Cheng Yang; Ming-Chih Shih; Jiannyeu Chen; Jun-Yi Yang; Peter Chesson; Chiou-Rong Sheue (Journal of Plant Research, 2018)

Protein-bounded uremic toxin p-cresylsulfate induces vascular permeability alternations - Wei-Hua Tang; Chao-Ping Wang; Teng-Hung Yu; Pei-Yang Tai; Shih-Shin Liang; Wei-Chin Hung; Cheng-Ching Wu; Sung-Hao Huang; Yau-Jiunn Lee; Shih-Chieh Chen (Histochemistry and Cell Biology, 2018)

Epirubicin induces apoptosis in osteoblasts through death-receptor and mitochondrial pathways - Tzu-Ching Huang; Pu-Rong Chiu; Wen-Tsan Chang; Bau-Shan Hsieh; Yu-Ci Huang; Hsiao-Ling Cheng; Li-Wen Huang; Yu-Chen Hu; Kee-Lung Chang (Apoptosis, 2018)

Tributyltin exposure at noncytotoxic doses dysregulates pancreatic β-cell function in vitro and in vivo - Ya-Wen Chen; Kuo-Cheng Lan; Jing-Ren Tsai; Te-I Weng; Ching-Yao Yang; Shing-Hwa Liu (Archives of Toxicology, 2017)

Cytoplasmic aryl hydrocarbon receptor regulates glycogen synthase kinase 3 beta, accelerates vimentin degradation, and suppresses epithelial–mesenchymal transition in non-small cell lung cancer cells - Ching-Hao Li; Chen-Wei Liu; Chi-Hao Tsai; Yi-Jen Peng; Yu-Hsuan Yang; Po-Lin Liao; Chen-Chen Lee; Yu-Wen Cheng; Jaw-Jou Kang (Archives of Toxicology, 2017)

Status quo of management of the human tissue banks in Taiwan - Ching-Pang Chou; Szu-Cheng Chou; Ying-Hua Chen; Yu-Hsuan Chen; Ming-Shin Lee (Cell and Tissue Banking, 2017)

Improved survival in patients with severe tuberculosis after exposure to fluoroquinolones - Shyh-Ren Chiang; Jiunn-Min Shieh; Chung-Hua Chen; Shu-Chen Hsing; Shih-Feng Wen; Jhi-Joung Wang; Kuo-Chen Cheng; Yin-Ching Chuang (Infectious Diseases, 2016)

Identification of susceptibility gene associated with female primary Sjögren’s syndrome in Han Chinese by genome-wide association study - I-Wen Song; Hsiang-Cheng Chen; Yuh-Feng Lin; Jenn-Hwai Yang; Chi-Ching Chang; Chung-Tei Chou; Ming-Ta Michael Lee; Yi-Chun Chou; Chien-Hsiun Chen; Yuan-Tsong Chen; Chen-Hung Chen; Jer-Yuarn Wu (Human Genetics, 2016)

Zonal management of multi-purposes groundwater utilization based on water quality and impact on the aquifer - Ching-Ping Liang; Cheng-Shin Jang; Ching-Fang Chen; Jui-Sheng Chen (Environmental Monitoring and Assessment, 2016)

Curcumin downregulates p38 MAPK-dependent X-ray repair cross-complement group 1 (XRCC1) expression to enhance cisplatin-induced cytotoxicity in human lung cancer cells - Chun-Liang Tung; Yi-Jun Jian; Jyh-Cheng Chen; Tai-Jing Wang; Wen-Ching Chen; Hao-Yu Zheng; Po-Yuan Chang; Kai-Sheng Liao; Yun-Wei Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Preclinical Pharmacokinetics Study of R- and S-Enantiomers of the Histone Deacetylase Inhibitor, AR-42 (NSC 731438), in Rodents - Hao Cheng; Zhiliang Xie; William P. Jones; Xiaohui Tracey Wei; Zhongfa Liu; Dasheng Wang; Samuel K. Kulp; Jiang Wang; Christopher C. Coss; Ching-Shih Chen; Guido Marcucci; Ramiro Garzon; et al. (The AAPS Journal, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Developing a reliable model for aquifer vulnerability - Cheng-Shin Jang; Chien-Wen Lin; Ching-Ping Liang; Jui-Sheng Chen (Stochastic Environmental Research and Risk Assessment, 2016)

G206D Mutation of Presenilin-1 Reduces Pen2 Interaction, Increases Aβ42/Aβ40 Ratio and Elevates ER Ca2+ Accumulation - Wei-Ting Chen; Yi-Fang Hsieh; Yan-Jing Huang; Che-Ching Lin; Yen-Tung Lin; Yu-Chao Liu; Cheng-Chang Lien; Irene Han-Juo Cheng (Molecular Neurobiology, 2015)

Identifications and removal of diurnal and semidiurnal variations in radon time series data of Hsinhua monitoring station in SW Taiwan using singular spectrum analysis - Arvind Kumar; Vivek Walia; Baldev Raj Arora; Tsanyao Frank Yang; Shih-Jung Lin; Ching-Chou Fu; Cheng-Hong Chen; Kuo-Liang Wen (Natural Hazards, 2015)

Associations between TRPV4 genotypes and body mass index in Taiwanese subjects - De-Min Duan; Semon Wu; Lung-An Hsu; Ming-Sheng Teng; Jeng-Feng Lin; Yu-Chen Sun; Ching-Feng Cheng; Yu-Lin Ko (Molecular Genetics and Genomics, 2015)

Robot-Assisted Passive Exercise for Ankle Hypertonia in Individuals with Chronic Spinal Cord Injury - Chia-Ying Fang; Miao-Ju Hsu; Chih-Chung Chen; Hsin-Yi Kathy Cheng; Ching-Chieh Chou; Ya-Ju Chang (Journal of Medical and Biological Engineering, 2015)

Rapid detection of copper chlorophyll in vegetable oils based on surface-enhanced Raman spectroscopy - Wei-Nan Lian; Jessie Shiue; Huai-Hsien Wang; Wei-Chen Hong; Po-Han Shih; Chao-Kai Hsu; Ching-Yi Huang; Cheng-Rong Hsing; Ching-Ming Wei; Juen-Kai Wang; Yuh-Lin Wang (Food Additives & Contaminants: Part A, 2015)

The Akt inhibitor MK-2206 enhances the cytotoxicity of paclitaxel (Taxol) and cisplatin in ovarian cancer cells - Ying-Hsi Lin; Bert Yu-Hung Chen; Wei-Ting Lai; Shao-Fu Wu; Jih-Hwa Guh; Ann-Lii Cheng; Lih-Ching Hsu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

TGF-β1 mediates the radiation response of prostate cancer - Chun-Te Wu; Ching-Chuan Hsieh; Tzu-Chen Yen; Wen-Cheng Chen; Miao-Fen Chen (Journal of Molecular Medicine, 2015)

Allyl isothiocyanate (AITC) inhibits pregnane X receptor (PXR) and constitutive androstane receptor (CAR) activation and protects against acetaminophen- and amiodarone-induced cytotoxicity - Yun-Ping Lim; Ching-Hao Cheng; Wei-Cheng Chen; Shih-Yu Chang; Dong-Zong Hung; Jih-Jung Chen; Lei Wan; Wei-Chih Ma; Yu-Hsien Lin; Cing-Yu Chen; Tsuyoshi Yokoi; Miki Nakajima; et al. (Archives of Toxicology, 2015)

The Association of RAB18 Gene Polymorphism (rs3765133) with Cerebellar Volume in Healthy Adults - Chih-Ya Cheng; Albert C. Yang; Chu-Chung Huang; Mu-En Liu; Ying-Jay Liou; Jaw-Ching Wu; Shih-Jen Tsai; Ching-Po Lin; Chen-Jee Hong (The Cerebellum, 2014)

Maintenance of human adipose derived stem cell (hASC) differentiation capabilities using a 3D culture - Ching-Yu Lin; Chi-Hui Huang; Yuan-Kun Wu; Nai-Chen Cheng; Jiashing Yu (Biotechnology Letters, 2014)

Design, synthesis, and evaluation of fluorescent cell-penetrating peptidic antagonists of Grb2-SH2 for targeting MCF-7 breast cancer cells - Yu-Cheng Hsiao; Chen-Yu Lee; Yi-Jhen Lin; Shu-Huai Tsai; Kee-Ching G. Jeng; Wei-Ting Chao; Feng-Di T. Lung (Medicinal Chemistry Research, 2013)

Probabilistic health risk assessment for ingestion of seafood farmed in arsenic contaminated groundwater in Taiwan - Ching-Ping Liang; Cheng-Shin Jang; Jui-Sheng Chen; Sheng-Wei Wang; Jin-Jing Lee; Chen-Wuing Liu (Environmental Geochemistry and Health, 2013)

The integration of nautical hazard assessment and harbor GIS models to the Taichung Port area in Taiwan - Cheng-Wu Chen; Ching-Chung Lee; Chia-Hung Chen; Chun-Pin Tseng (Natural Hazards, 2013)

Erratum to: Significance of IL-6 in the transition of hormone-resistant prostate cancer and the induction of myeloid-derived suppressor cells - Chun-Te Wu; Ching-Chuan Hsieh; Cheng-Chia Lin; Wen-Cheng Chen; Ji-Hong Hong; Miao-Fen Chen (Journal of Molecular Medicine, 2013)

Hyperinakin, a new anti-inflammatory phloroglucinol derivative from Hypericum nakamurai - Yuan-Bin Cheng; Ahmed Eid Fazary; Yu-Chi Lin; I-Wen Lo; Seow-Chin Ong; Shun-Ying Chen; Ching-Te Chien; Yen-Jung Lin; Wan-Wan Lin; Ya-Ching Shen (Natural Product Research, 2013)

Application of GIS for the determination of hazard hotspots after direct transportation linkages between Taiwan and China - Cheng-Wu Chen; Ching-Chung Lee; Chun-Pin Tseng; Chia-Hung Chen (Natural Hazards, 2013)

MicroRNA-210 targets antiapoptotic Bcl-2 expression and mediates hypoxia-induced apoptosis of neuroblastoma cells - Chung-Ching Chio; Jia-Wei Lin; Heien-An Cheng; Wen-Ta Chiu; Yuan-Hung Wang; Jhi-Joung Wang; Chung-Hsi Hsing; Ruei-Ming Chen (Archives of Toxicology, 2013)

Glycogen synthase kinase-3β inactivation is an intracellular marker and regulator for endotoxemic neutrophilia - Tsan-Tzu Yang; Chia-Ling Chen; Wei-Chieh Lin; Yee-Shin Lin; Po-Chun Tseng; Chia-Yuan Hsieh; Yu-Hong Chen; Wei-Ching Huang; Cheng-Chieh Tsai; Chi-Yun Wang; Chi-Chang Shieh; Chiou-Feng Lin (Journal of Molecular Medicine, 2013)

Recombined sequences between the non-coding control regions of JC and BK viruses found in the urine of a renal transplantation patient - Yu-Ching Liaw; Cheng-Hsu Chen; Kuo-Hsiung Shu; Chiung-Yao Fang; Wei-Chih Ou; Pei-Lain Chen; Cheng-Huang Shen; Mien-Chun Lin; Deching Chang; Meilin Wang (Virus Genes, 2012)

Significance of IL-6 in the transition of hormone-resistant prostate cancer and the induction of myeloid-derived suppressor cells - Chun-Te Wu; Ching-Chuan Hsieh; Cheng-Chia Lin; Wen-Cheng Chen; Ji-Hong Hong; Miao-Fen Chen (Journal of Molecular Medicine, 2012)

The effects of a sudden salinity change on cortisol, glucose, lactate, and osmolality levels in grouper Epinephelus malabaricus - Wen-Ching Tsui; Jiann-Chu Chen; Sha-Yen Cheng (Fish Physiology and Biochemistry, 2012)

Interplay of RsbM and RsbK controls the σ B activity of Bacillus cereus - Lei‐Chin Chen; Jung‐Chi Chen; Jwu‐Ching Shu; Chien‐Yen Chen; Ssu‐Ching Chen; Shu‐Hwa Chen; Chun‐Yen Lin; Chi‐Yu Lu; Chien‐Cheng Chen (Environmental Microbiology, 2012)
Summary The alternative transcription factor σ B of Bacillus cereus controls the expression of a number of genes that respond to environmental stress. Four proteins encoded in the sigB gene cluster, including RsbV, RsbW, RsbY (RsbU) and RsbK, are known to be essential in the σ B ‐mediated stress response. In the context of stress, the hybrid sensor kinase RsbK is thought to phosphorylate the response regulator RsbY, a PP2C serine phosphatase, leading to the dephosphorylation of the phosphorylated RsbV. The unphosphorylated RsbV then sequesters the σ B antagonist, RsbW, ultimately liberating σ B . The gene arrangement reveals an open reading frame, bc1007 , flanked immediately downstream by rsbK within the sigB gene cluster. However, little is known about the function of bc1007 . In this study, the deletion of bc1007 resulted in high constitutive σ B expression independent of environmental stimuli, indicating that bc1007 plays a role in σ B regulation. A bacterial two‐hybrid analysis demonstrated that BC1007 interacts directly with RsbK, and autoradiographic studies revealed a specific C 14 ‐methyl transfer from the radiolabelled S‐adenosylmethionine to RsbK when RsbK was incubated with purified BC1007. Our data suggest that BC1007 (RsbM) negatively regulates σ B activity by methylating RsbK. Additionally, mutagenic substitution was employed to modify 12 predicted methylation residues in RsbK. Certain RsbK mutants were able to rescue σ B activation in a rsbK ‐deleted bacterial strain, but RsbK E439A failed to activate σ B , and RsbK E446A only moderately induced σ B . These results suggest that Glu439 is the preferred methylation site and that Glu446 is potentially a minor methylation site. Gene arrays of the rsbK orthologues and the neighbouring rsbM orthologues are found in a wide range of bacteria. The regulation of sigma factors through metylation of RsbK‐like sensor kinases appears to be widespread in the microbial world.

Polycyclic aromatic hydrocarbons in household dust near diesel transport routes - Chung-Yih Kuo; Heng-Chun Chen; Fang-Ching Cheng; Li-Ru Huang; Po-Shan Chien; Jing-Ya Wang (Environmental Geochemistry and Health, 2012)

Climate change, sea level rise and rice: global market implications - Chi-Chung Chen; Bruce McCarl; Ching-Cheng Chang (Climatic Change, 2012)

Rilmenidine improves hepatic steatosis through p38-dependent pathway to higher the expression of farnesoid X receptor - Po-Sheng Yang; Hung-Tsung Wu; Hsien-Hui Chung; Chun-Ta Chen; Chin-Wen Chi; Ching-Hua Yeh; Juei-Tang Cheng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

An integrated flood risk assessment model for property insurance industry in Taiwan - Wen-Ko Hsu; Pei-Chiung Huang; Ching-Cheng Chang; Cheng-Wu Chen; Dung-Moung Hung; Wei-Ling Chiang (Natural Hazards, 2011)

Inorganic arsenic causes cell apoptosis in mouse cerebrum through an oxidative stress-regulated signaling pathway - Cheng Chien Yen; Tsung Jung Ho; Chin Ching Wu; Chun Fang Chang; Chin Chuan Su; Ya Wen Chen; Tzyy Rong Jinn; Tien Hui Lu; Po Wen Cheng; Yi Chang Su; Shing Hwa Liu; Chun Fa Huang (Archives of Toxicology, 2011)

Synthesis of Highly Selective Indole-Based Sensors for Mercuric Ion - Huei-Jyun Huang; Jiun-Ly Chir; Hsiu-Jung Cheng; Shau-Jiun Chen; Ching-Han Hu; An-Tai Wu (Journal of Fluorescence, 2011)

Characterization and prediction of mRNA polyadenylation sites in human genes - Tzu-Hao Chang; Li-Ching Wu; Yu-Ting Chen; Hsien-Da Huang; Baw-Jhiune Liu; Kuang-Fu Cheng; Jorng-Tzong Horng (Medical & Biological Engineering & Computing, 2011)

Analysis of genetic variations in the dopamine D1 receptor (DRD1) gene and antipsychotics-induced tardive dyskinesia in schizophrenia - I-Ching Lai; Geng-Han Mo; Mao-Liang Chen; Ying-Chieh Wang; Jen-Yeu Chen; Ding-Lieh Liao; Ya-Mei Bai; Chao-Cheng Lin; Tzu-Ting Chen; Ying-Jay Liou (European Journal of Clinical Pharmacology, 2011)

Role of DNA methyltransferase 1 in hormone-resistant prostate cancer - Miao-Fen Chen; Wen-Cheng Chen; Yu-Jia Chang; Ching-Fang Wu; Chun-Te Wu (Journal of Molecular Medicine, 2010)

Proteomic Analysis of the Effect of Cyanide on Klebsiella oxytoca - Petrus Tang; You-Cheng Hseu; Hui-Hsuan Chou; Kuo-Yang Huang; Ssu Ching. Chen (Current Microbiology, 2010)

Cloning and Characterization of ApRab4, a Recycling Rab Protein of Aiptasia pulchella, and Its Implication in the Symbiosome Biogenesis - Ming-Cheng Hong; Yung-Sen Huang; Pa-Ching Song; Wen-Wen Lin; Lee-Shing Fang; Ming-Chyuan Chen (Marine Biotechnology, 2009)

Classifying Cinnamomums using rough sets classifier based on interval-discretization - Ching-Hsue Cheng; Yao-Hsien Chen; Jing-Wei Liu (Plant Systematics and Evolution, 2009)

Effect of metal binding and posttranslational lysine carboxylation on the activity of recombinant hydantoinase - Cheng-Yang Huang; Ching-Chen Hsu; Mei-Chun Chen; Yuh-Shyong Yang (JBIC Journal of Biological Inorganic Chemistry, 2009)

Estimating the economic impacts of climate change on infectious diseases: a case study on dengue fever in Taiwan - Wei-Chun Tseng; Chi-Chung Chen; Ching-Cheng Chang; Yu-Hsien Chu (Climatic Change, 2009)

Mana-Hox displays anticancer activity against prostate cancer cells through tubulin depolymerization and DNA damage stress - Che-Jen Hsiao; Yunn-Fang Ho; John T.-A. Hsu; Wei-Ling Chang; Yi-Cheng Chen; Ya-Ching Shen; Ping-Chiang Lyu; Jih-Hwa Guh (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Time to rehospitalization in patients with bipolar I disorder on lithium or valproate with adjunctive antipsychotics - Ching-Hua Lin; Ching-Wen Huang; Cheng-Chung Chen; Yu-Fen Hsu; Wen-Ho Chang; Hsien-Yuan Lane (Psychopharmacology, 2008)

Pravastatin attenuates carboplatin-induced cardiotoxicity via inhibition of oxidative stress associated apoptosis - Ching-Feng Cheng; Shu-Hui Juan; Jin-Jer Chen; Ying-Chi Chao; His-Hsien Chen; Wei-Shiung Lian; Chun-Yi Lu; Chung-I Chang; Ted-H Chiu; Heng Lin (Apoptosis, 2008)

Gene expression variation increase in trisomy 21 tissues - Ching Yu Chou; Li Yu Liu; Chien Yu Chen; Cheng Hsien Tsai; Hsiao Lin Hwa; Li Yun Chang; Yi Shing Lin; Fon Jou Hsieh (Mammalian Genome, 2008)

Changes in hydrogeological properties of the River Choushui alluvial fan aquifer due to the 1999 Chi-Chi earthquake, Taiwan - Cheng-Shin Jang; Chen-Wuing Liu; Yeeping Chia; Li-Hsin Cheng; You-Ching Chen (Hydrogeology Journal, 2008)

Single Strand DNA Breaks in Human Lymphocytes Exposed to para-Phenylenediamine and its Derivatives - Soi Mei Chye; You Cheng Hseu; Shih-Hsiung Liang; Chin-Hui Chen; Ssu Ching Chen (Bulletin of Environmental Contamination and Toxicology, 2008)

Glycated type 1 collagen induces endothelial dysfunction in culture - Pei-Ching Kuo; Cheng-Heng Kao; Jan-Kan Chen (In Vitro Cellular & Developmental Biology - Animal, 2007)

Two new xeniolides from a Taiwanese Xenia soft coral - Ya-Ching Shen; Yu-Hui Chen; Yuan-Bin Cheng; Yao Haur Kuo; Ashraf Taha Khalil (Natural Product Research, 2007)

Delimitation of arsenic-contaminated groundwater using risk-based indicator approaches around blackfoot disease hyperendemic areas of southern Taiwan - Cheng-shin Jang; Chen-wuing Liu; Kuang-liang Lu; Ching-chieh Lin (Environmental Monitoring and Assessment, 2007)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

Inhibition of Cyanide-Insensitive Respiration in Klebsiella oxytoca SYSU-011 by 8-Hydroxyquinolone - Chih Ming Kao; You Cheng Hseu; Yen Ling Huang; Peturs Tang; Ssu Ching Chen (Current Microbiology, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

A fine physical map of the rice chromosome 5 - Chia-Hsiung Cheng; Mei-Chu Chung; Shu-Mei Liu; Shi-Kuang Chen; Fang-Yi Kao; Shu-Jen Lin; Shin-Hsin Hsiao; I-Chieh Tseng; Yue-Ie C. Hsing; Hong-Pang Wu; Ching-San Chen; Jei-Fu Shaw; et al. (Molecular Genetics and Genomics, 2005)

Polymorphism for Transforming Growth Factor Beta 1-509 (TGF-B1-509): Association with Endometriosis - Yao-Yuan Hsieh; Chi-Chen Chang; Fuu-Jen Tsai; Ching-Tien Peng; Lian-Shun Yeh; Cheng-Chieh Lin (Biochemical Genetics, 2005)

Inhibitory effect of resveratrol on angiotensin II-induced cardiomyocyte hypertrophy - Tzu-Hurng Cheng; Ju-Chi Liu; Heng Lin; Neng-Lang Shih; Yen-Ling Chen; Meng-Ting Huang; Paul Chan; Ching-Feng Cheng; Jin-Jer Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)

Alpha-naphthoflavone induces vasorelaxation through the induction of extracellular calcium influx and NO formation in endothelium - Yu-Wen Cheng; Ching-Hao Li; Chen-Chen Lee; Jaw-Jou Kang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2003)

Microsatellite polymorphism in promoter of heme oxygenase-1 gene is associated with susceptibility to coronary artery disease in type 2 diabetic patients - Ying-Hwa Chen; Shing-Jong Lin; Ming-Wei Lin; Hui-Ling Tsai; San-San Kuo; Jaw-Wen Chen; Min-Ji Charng; Tao-Cheng Wu; Lung-Ching Chen; Philip Ding; Wen-Harn Pan; Yuh-Shan Jou; et al. (Human Genetics, 2002)

Improvement of phytase thermostability by using sorghum liquor wastes supplemented with starch - Chang-Chih Chen; Ching-Tsan Hunag; Kou-Joan Cheng (Biotechnology Letters, 2001)

Specific protein phosphorylation induced in Xanthomonas campestris pv. oryzae by bacteriophage Xp12 - Ching-Ming Cheng; Jenn Tu; Chen-Chung Yang; Tsong-Teh Kuo (Archives of Microbiology, 1994)

Specific protein phosphorylation induced in Xanthomonas campestris pv. oryzae by bacteriophage Xp12 - Tsong-Teh Kuo; Ching-Ming Cheng; Jenn Tu; Chen-Chung Yang (Archives of Microbiology, 1994)